Contribution and obstacle analysis of applying BIM in promoting green buildings. (1st January 2021) - Huang, Beijia; Lei, Jinming; Ren, Fumin; Chen, Yanxi; Zhao, Quanze; Li, Shenhao; Lin, Yang
Abstract: BIM (Building Information Modeling) is now a widely used tool for architecture, engineering and civil engineering. The application of BIM technology can help improve the efficiency of the construction industry and help evaluating the sustainability aspects of green buildings. However, our literature review finds that the contribution and obstacles of applying BIM for promoting green buildings have not been clearly analyzed. In order to better promote the development of BIM technology, this study explored the contribution of BIM to green building and the obstacles of BIM in the promotion of green building in the form of questionnaire survey of different stakeholders. On the basis of the literature research, we design a questionnaire consisting of 27 questions. In the next step, the questionnaires are distributed to 300 relevant stakeholders of BIM and green buildings. Interviewees mainly cover the building designers, construction company managers, and workers in green buildings certification company. Then SPSS and AMOS software were used to test the reliability and validity of the questionnaire to ensure the availability of the results. According to the questionnaire feedback, BIM technology has made important contributions in the design stage, construction stage and other aspects of green buildings. At the same time, we summarize the most urgent barriers from four aspects of technology, management, economy and social environment. Besides distinguishing barriers, we also rank the severity of barriers for different stakeholders, so as to propose more targeted countermeasures.